Targeting Bcl6 in the TREX1 D18N murine model ameliorates autoimmunity by modulating T‐follicular helper cells and germinal center B cells. Issue 5 (15th February 2022) - Venkatadri, Rajkumar; Sabapathy, Vikram; Dogan, Murat; Mohammad, Saleh; Harvey, Scott E.; Simpson, Sean R.; Grayson, Jason M.; Yan, Nan; Perrino, Fred W.; Sharma, Rahul
Abstract: The Three Prime Repair EXonuclease I (TREX1) is critical for degrading post‐apoptosis DNA. Mice expressing catalytically inactive TREX1 (TREX1 D18N) develop lupus‐like autoimmunity due to chronic sensing of undegraded TREX1 DNA substrates, production of the inflammatory cytokines, and the inappropriate activation of innate and adaptive immunity. This study aimed to investigate Thelper (Th) dysregulation in the TREX1 D18N model system as a potential mechanism for lupus‐like autoimmunity. Comparison of immune cells in secondary lymphoid organs, spleen and peripheral lymph nodes (LNs) between TREX1 D18N mice and the TREX1 null mice revealed that the TREX1 D18N mice exhibit a Th1 bias. Additionally, the T‐follicular helper cells (Tfh) and the germinal celter (GC) B cells were also elevated in the TREX1 D18N mice. Targeting Bcl6, a lineage‐defining transcription factor for Tfh and GC B cells, with a commercially available Bcl6 inhibitor, FX1, attenuated Tfh, GC, and Th1 responses, and rescued TREX1 D18N mice from autoimmunity. The study presents Tfh and GC B‐cell responses as potential targets in autoimmunity and that Bcl6 inhibitors may offer therapeutic approach in TREX1‐associated or other lupus‐like diseases. Abstract : Defects in DNA degrading enzyme such as TREX1 induce immune dysregulation that includes a Th1 bias as well as increase in T‐follicular helper (TfH) and germinal center (GC) B‐cells leading to autoimmune disease. This study offers the potential of using Bcl6 inhibition for restoring immune homeostasis and rescuing from autoimmunity.